Electrophysiologic and molecular mechanisms of a frameshift NPPA mutation linked with familial atrial fibrillation. (July 2019) - Menon, Ambili; Hong, Liang; Savio-Galimberti, Eleonora; Sridhar, Arvind; Youn, Seock-Won; Zhang, Meihong; Kor, Kaylen; Blair, Marcia; Kupershmidt, Sabina; Darbar, Dawood
Abstract: A frameshift (fs) mutation in the natriuretic peptide precursor A ( NPPA ) gene, encoding a mutant atrial natriuretic peptide (Mut-ANP), has been linked with familial atrial fibrillation (AF) but the underlying mechanisms by which the mutation causes AF remain unclear. We engineered 2 transgenic (TG) mouse lines expressing the wild-type (WT)- NPPA gene ( H-WT-NPPA ) and the human fs-Mut- NPPA gene ( H-fsMut-NPPA ) to test the hypothesis that mice overexpressing the human NPPA mutation are more susceptible to AF and elucidate the underlying electrophysiologic and molecular mechanisms. Transthoracic echocardiography and surface electrocardiography (ECG) were performed in H-fsMut-NPPA, H-WT-NPPA, and Non-TG mice. Invasive electrophysiology, immunohistochemistry, Western blotting and patch clamping of membrane potentials were performed. To examine the role of the Mut-ANP in ion channel remodeling, we measured plasma cyclic guanosine monophosphate (cGMP) and cyclic adenosine monophosphate (cAMP) levels and protein kinase A (PKA) activity in the 3 groups of mice. In H-fsMut-NPPA mice mean arterial pressure (MAP) was reduced when compared to H-WT-NPPA and Non-TG mice. Furthermore, injection of synthetic fs-Mut-ANP lowered the MAP in H-WT-NPPA and Non-TG mice while synthetic WT-ANP had no effect on MAP in the 3 groups of mice. ECG characterization revealed significantly prolonged QRS duration in H-fsMut-NPPA mice when compared to the other two groups. Trans -Esophageal (TE) atrial pacing of H-fsMut-NPPA mice showed increased AF burden and AF episodes when compared with H-WT-NPPA or Non-TG mice. The cardiac Na + (NaV1.5) and Ca 2+ (CaV1.2/CaV1.3) channel expression and currents ( I Na, I CaL ) and action potential durations (APD90 /APD50 /APD20 ) were significantly reduced in H-fsMut-NPPA mice while the rectifier K + channel current ( I Ks ) was markedly increased when compared to the other 2 groups of mice. In addition, plasma cGMP levels were only increased in H-fsMut-NPPA mice with a corresponding reduction in plasma cAMP levels and PKA activity. In summary, we showed that mice overexpressing an AF-linked NPPA mutation are more prone to develop AF and this risk is mediated in part by remodeling of the cardiac Na +, Ca 2+ and K + channels creating an electrophysiologic substrate for reentrant AF. Highlights: The underlying mechanisms by which an NPPA mutation causes AF are poorly understood. We engineered 2 transgenic mouse models expressing the wild-type and humanized NPPA mutation. Mice expressing the NPPA mutation were more prone to AF. This risk was mediated by remodeling of cardiac Na +, Ca 2+ and K + channels creating a substrate for AF.